Midwifery Care for Third Trimester Pregnant Women with Back Pain Discomfort in Clinics and Maternity Homes: Asuhan Kebidanan Pada Ibu Hamil Trimester III dengan Ketidaknyamanan Nyeri Punggung di Klinik dan Rumah Bersalin - Anggraeni, Diah Putri; Rusdyati, Tutik; K, Paramitha Amelia (Universitas Muhammadiyah Sidoarjo, 2020)
Pregnancy is the period from conception to delivery of the fetus. During pregnancy, women will experience changes both anatomically and physiologically. This causes discomfort to pregnant women. The aim is to find out the description of back pain in the third trimester of pregnancy at the Delta Mutiara Clinic and Maternity Home on January 7, 2020. The results of 60-90% studies in 2018 experienced back pain in pregnant women. This article uses a descriptive method that aims to create an objective picture of the situation, from all data collection with patient history, examination, data analysis and documentation. The results of the anamnesis showed that the pregnant woman is currently 9 months old with low back pain, the results of the examination of the mother's general condition are good and did not find any problems, so that she can conclude the analysis and be given appropriate management such as how to overcome the discomfort of back pain in pregnant women. From all the data that has been collected, it can be concluded that the condition of the mother and baby are in good condition with the discomfort of back pain.